(untitled) (Scientific journal of the Fergana State University, 2023)
The authors of this study aim to develop a synergetic concept of pedagogical diagnosis of conflict-based behavior of students of higher education institutions. It describes the sequence of four sub-structures according to the concept of the dynamic structure of personality, their importance and the inherent dependence of the emergence of conflicts on these sub-structures. Conflict-causing behavior in the educational process, conflicting parties, their interaction, possibilities of conflict prevention and mitigating conflict situations, in addition, the importance of objectivity in their elimination, conflict management as a whole system studied. During the research, the synergistic theoretical bases of conflicts were analyzed based on various theories and concepts based on the interpretation of conflicts in the social environment of higher education, such as the macro-social approach, as well as the possibility of successfully organizing the pedagogical process in educating the young generation as a perfect person in educational institutions. practical recommendations on prevention and elimination of pedagogical disputes have been developed. A synergetic model of conflict resolution was developed as a result of pedagogical diagnosis of students’ behavior in conflict situations that arise between students of higher education institutions.